A powerful double radio relic system discovered in PSZ1 G108.18-11.53: evidence for a shock with non-uniform Mach number?. Issue 4 (9th September 2015) - de Gasperin, F.; Intema, H. T.; van Weeren, R. J.; Dawson, W. A.; Golovich, N.; Wittman, D.; Bonafede, A.; Brüggen, M.
Abstract: Diffuse radio emission in the form of radio haloes and relics has been found in a number of merging galaxy clusters. These structures indicate that shock and turbulence associated with the merger accelerate electrons to relativistic energies. We report the discovery of a radio relic + radio halo system in PSZ1 G108.18-11.53 ( z  = 0.335). This cluster hosts the second most powerful double radio relic system ever discovered. We observed PSZ1 G108.18-11.53 with the Giant Meterwave Radio Telescope and the Westerbork Synthesis Radio Telescope. We obtained radio maps at 147, 323, 607 and 1380 MHz. We also observed the cluster with the Keck telescope, obtaining the spectroscopic redshift for 42 cluster members. From the injection index, we obtained the Mach number of the shocks generating the two radio relics. For the southern shock, we found $\mathcal {M}= 2.33^{+0.19}_{-0.26}$, while the northern shock Mach number goes from $\mathcal {M}= 2.20^{+0.07}_{-0.14}$ in the north part down to $\mathcal {M}= 2.00^{+0.03}_{-0.08}$ in the southern region. If the relation between the injection index and the Mach number predicted by diffusive shock acceleration theory holds, this is the first observational evidence for a gradient in the Mach number along a galaxy cluster merger shock.